LANDASAN PENDIDIKAN AGAMA ISLAM DENGAN PROFIL PELAJAR PANCASILA DI ERA KURIKULUM MERDEKA - Afnanda, Mihrab (Fakultas Tarbiyah IAI Darussalam, 2023)
Abstract The first precepts to the fifth precepts contain the foundation of Islamic religious education in the independent curriculum which also places the status of